New A-homo lactam D-homo lactone androstane derivative: Synthesis and evaluation of cytotoxic and anti-inflammatory activities in vitro - Savić, Marina P; Škorić, Dušan Đ; Kuzminac, Ivana Z; Jakimov, Dimitar S; Kojić, Vesna V; Rárová, Lucie; Strnad, Miroslav; Djurendić, Evgenija A (Steroids, 2020)
This paper describes the synthesis of a new A-homo lactam D-homo lactone androstane derivative from dehydroepiandrosterone. To evaluate the impact of the introduction of nitrogen in the parental scaffold on biological activity, a new androstane enamide-type lactam derivative was prepared and characterized. The new compound as well as starting compounds were screened for cytotoxic, anti-angiogenic and anti-inflammatory activities using several human cancer cell lines (MCF-7, MDA-MB-231, PC3, CEM, G-361, HeLa), endothelial (HUVEC) and non-tumour (MRC-5 and BJ) cell lines. Strong cytotoxic and anti-inflammatory activity with a broad therapeutical window was demonstrated by the A-homo lactam D-homo lactone androstane derivative. The induction of apoptosis in treated PC3 cultures was confirmed using apoptotic morphology screening and a fluorescent double-staining method. New A-homo lactam D-homo lactone androstane derivative induced apoptosis more than the tested reference compounds, Formestane and Doxorubicin. An in silico ADME analysis showed that the compounds possess drug-like properties.
Keywords: antiflogistika; proliferace buněk; apoptóza; vztah mezi dávkou a účinkem léčiva; molekulární konformace; Apoptotic morphology; optické zobrazování; Apoptosis; screeningové testy protinádorových léčiv; Anti-angiogenic activity; fytogenní protinádorové látky; E-Selectin; E-selektin; Structure-Activity Relationship; lidé; Optical Imaging; kultivované buňky; Molecular Conformation; Structural analysis; laktony; Antineoplastic Agents, Phytogenic; Humans; Cells, Cultured; Dose-Response Relationship, Drug; Cytotoxic activity; ADME analysis in silico; Anti-inflammatory activity; Anti-Inflammatory Agents; androstany; Cell Proliferation; vztahy mezi strukturou a aktivitou; Drug Screening Assays, Antitumor; Lactones; Androstanes